Counterfactual thinking within the first year after sexual assault: examining associations with posttraumatic stress reactions in the Norwegian TRUST-study - Ines Blix; Alf Børre Kanten; Tore Wentzel-Larsen; Andrea Undset; Andrea Rustand; Siri Thoresen (European Journal of Psychotraumatology)
Background: Counterfactual thinking (CFT), involves mental simulations of alternative outcomes to past events (e.g. ‘What if … ’ or ‘If only … ’), and is commonly observed after trauma. While CFT can be adaptive, it is also linked to psychological distress, including posttraumatic stress reactions (PTSR).Objective: The present study aims to examine the relationship between the frequency and vividness of upward and downward counterfactual thoughts and PTSR, in the recent aftermath of sexual assault (SA).Method: The sample consisted of 327 women who had experienced SA within the last year. PTSR was measured using the International Trauma Questionnaire (ITQ), while CFT was assessed through self-reported frequency and vividness of upward (event could have been less severe or avoided) and downward (event could have been worse) counterfactual thoughts.Results: The results revealed a significant difference in the distribution of upward versus downward CFT. Specifically, more participants reported engaging in upward CFT ‘Very Often’ and ‘Often,’ while downward CFT was reported less frequently. Vividness was higher for downward CFT. Both frequency and vividness of upward and downward counterfactuals were significantly associated with higher levels of PTSR.Conclusion: The present findings highlight the role of counterfactual thinking in post-assault distress and emphasize the need for targeted interventions addressing CFT in the aftermath of trauma.